Methods and applications of the IW business survey - Michael Grömling (Institut der deutschen Wirtschaft (IW), 2018)
Surveys of businesses provide important data for an analysis of economic development. In addition to the statistical offices in the respective states, private sector institutions such as re-search institutes or associations provide a diverse range of economic data. The following article presents the business survey conducted by the German Economic Institute (Institut der deutschen Wirtschaft, IW). It provides comprehensive information on the current situation and the outlook of German companies and serves as an important basis for the half-year economic forecast by the German Economic Institute (Grömling, 2005).
Keywords: C82; E32; 330